2018
DOI: 10.1007/s12105-018-0939-x
|View full text |Cite
|
Sign up to set email alerts
|

Poorly Differentiated Clusters Predict a Poor Prognosis for External Auditory Canal Carcinoma

Abstract: Squamous cell carcinoma (SCC) of the external auditory canal (EAC) is rare and offers a poor prognosis; more accurate prognostic biomarkers are required. Our laboratory recently demonstrated that tumor budding, characterized by tumor cell clusters (< 5 cells), and laminin 5-γ2 staining of SCC of the EAC are associated with shorter survival. However, clusters composed of ≥ 5 tumor cells are also found in the stroma. Previous reports of colorectal cancer suggest that poorly differentiated clusters (PDCs) are a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Three studies have evaluated the prognostic significance of PDC in other carcinoma types, including Crohn's disease-associated small bowel adenocarcinoma, [54][55][56] breast carcinoma and auditory canal carcinoma, with all finding high PDC grade to be significantly associated with adverse clinical outcomes. Interestingly, PDC grade in breast and auditory canal carcinomas was associated with strong interobserver agreement (kappa values 0.74 and 0.89, respectively), similar to that reported for CRC.…”
Section: Significance Of Pdc In Non-cr Cancersmentioning
confidence: 99%
“…Three studies have evaluated the prognostic significance of PDC in other carcinoma types, including Crohn's disease-associated small bowel adenocarcinoma, [54][55][56] breast carcinoma and auditory canal carcinoma, with all finding high PDC grade to be significantly associated with adverse clinical outcomes. Interestingly, PDC grade in breast and auditory canal carcinomas was associated with strong interobserver agreement (kappa values 0.74 and 0.89, respectively), similar to that reported for CRC.…”
Section: Significance Of Pdc In Non-cr Cancersmentioning
confidence: 99%
“…The biomolecular or prognostic factors associated with PDCs are similar to those of TB 38 . However, in a previous study we found that, even in cases with low‐grade TB, SCC‐EAC patients with high‐grade PDCs had a poor prognosis 6 . Thus, in this study, we selected both markers of invasive morphology, TB and PDCs (Figure ), for detailed investigation.…”
Section: Discussionmentioning
confidence: 90%
“…In SCC-EAC, cancer clusters surrounded by stroma and composed of 5 or more cancer cells were defined as PDCs. 6,24,25 To quantify PDCs, the whole tumor was first scanned under low magnification to identify the area with the most PDCs in CK immunostained sections. Next, the clusters within the microscopic field of a 20× objective lens (WHK 10× ocular lens; Olympus) were counted.…”
Section: Assessment Of Pdc Gradementioning
confidence: 99%
See 1 more Smart Citation
“…MPP should be distinguished from poorly differentiated clusters (PDCs) and tumour budding (36). MPP generally consists of 3-20 cells with cleft-like spaces and without fibrovascular cores at the interface with the stroma (6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%